1997
DOI: 10.1016/s0042-6989(96)00227-1
|View full text |Cite
|
Sign up to set email alerts
|

Contour Integration Across Polarities and Spatial Gaps: From Local Contrast Filtering to Global Grouping

Abstract: This article introduces an experimental paradigm to selectively probe the multiple levels of visual processing that influence the formation of object contours, perceptual boundaries, and illusory contours. The experiments test the assumption that, to integrate contour information across space and contrast sign, a spatially short-range filtering process that is sensitive to contrast polarity inputs to a spatially long-range grouping process that pools signals from opposite contrast polarities. The stimuli consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 45 publications
2
38
1
Order By: Relevance
“…While Yu and Levi's (1997a) data show spatial facilitation with short targets and inducers within spatial limits up to 20 arcmin only, other findings with much longer targets and inducing lines indicate that spatial facilitation occurs within larger spatial scales as well (Dresp and Grossberg, 1997;Wehrhahn and Dresp, 1998). Here again, the conclusions are not straightforward.…”
Section: Length and Spatial Separation Of Targets And Inducersmentioning
confidence: 84%
See 3 more Smart Citations
“…While Yu and Levi's (1997a) data show spatial facilitation with short targets and inducers within spatial limits up to 20 arcmin only, other findings with much longer targets and inducing lines indicate that spatial facilitation occurs within larger spatial scales as well (Dresp and Grossberg, 1997;Wehrhahn and Dresp, 1998). Here again, the conclusions are not straightforward.…”
Section: Length and Spatial Separation Of Targets And Inducersmentioning
confidence: 84%
“…This surprising result may reflect the output of a mechanism of contour grouping that is activated only when the decreasing proximity of stimulus fragments is compensated by stronger local contrasts, whichever sign they carry. Dresp and Grossberg (1997) conducted spatial facilitation studies with edge-like inducers and fractioned line targets collinear with the orientation of the inducing edges. In some conditions, the contrast sign of half the target line was the same as that of the nearest inducer, in others it carried the opposite sign.…”
Section: Inducer Contrast and Contrast Polaritymentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on spatial facilitation have demonstrated that high-contrast-inducing lines facilitate the detection of a target line of either contrast polarity when the distance separating them is wider than 20 arcmin (Wehrhahn & Dresp, 1998). Experiments with edge-like inducers and collinear line targets demonstrated detection facilitation with shorter spatial separations, but only in conditions in which the inducers and the target had the same contrast polarity (Dresp & Grossberg, 1997). Clearly, the role of contrast polarity in contour integration is still an open question.…”
mentioning
confidence: 99%